Relationships between multivitamins, blood biochemistry markers, and BMC and BMD based on RF: A cross-sectional and population-based study of NHANES, 2017-2018. - Lijuan Xu; Mengqi Wu; Ying Zhang; Hongsheng Kun; Jiangbao Xu (PLoS ONE)
Background Previous studies have separately suggested a possible association between the vitamin exposure, blood biochemical indicators, and bone density. Our study aimed to investigate the relationship between vitamin exposure serum concentrations, blood biochemical indicator serum concentrations, and BMC and BMD using the NHANES 2017-2018 nutrient survey data. This population-based cross-sectional study aimed to explore these associations. Methods In this study, we measured vitamin serum concentrations, serum ion serum concentrations, and serum biochemical indicators in adults participating in the NHANES. Skeletal status was assessed by evaluating BMC and BMD in the whole body. Given the inclusion of multiple variables and diverse data types, we used the RF to fit a multivariable model to estimate the associations between vitamin serum concentrations, blood biochemical indicator serum concentrations, and skeletal status. Results Under the dimension reduction and comparison selection of RF model, we identified ALP, CPK, and creatinine serum concentrations as the most important factors associated with BMC and BMD in multiple skeletal sites, and the gender, age, height, weight, and body mass index which were found to be related to BMC and BMD in different skeletal sites. Vitamin D and blood calcium serum concentrations were not the important factors associated with BMC and BMD and the three blood biochemical indexes were more important than the vitamin level for BMC and BMD. Conclusion The effect of vitamin serum concentrations and blood calcium serum concentrations on human bone density was not significant. ALP, CPK and creatinine serum concentrations body development indicators were identified as the most important factors related to bone status. The RF model can be used to comprehensively evaluate the effects of vitamin content and blood biochemistry serum concentrations in adults on BMC and BMD.